IDNLearn.com offers a user-friendly platform for finding and sharing knowledge. Our community provides accurate and timely answers to help you understand and solve any issue.
Sagot :
Sure, let's simplify the given expression step-by-step.
Given: [tex]\(\sqrt{2a}\left(2 \sqrt{8a} + \sqrt{2a^3}\right)\)[/tex]
1. Simplify [tex]\(\sqrt{2a} \cdot 2\sqrt{8a}\)[/tex]
- First, consider [tex]\(\sqrt{8a}\)[/tex]:
[tex]\[ \sqrt{8a} = \sqrt{4 \cdot 2a} = \sqrt{4} \cdot \sqrt{2a} = 2\sqrt{2a} \][/tex]
- Next, multiply by 2:
[tex]\[ 2\sqrt{8a} = 2 \cdot 2\sqrt{2a} = 4\sqrt{2a} \][/tex]
2. Now, simplify [tex]\(\sqrt{2a} \cdot \sqrt{2a^3}\)[/tex]
- Consider [tex]\(\sqrt{2a^3}\)[/tex]:
[tex]\[ \sqrt{2a^3} = \sqrt{2a^2 \cdot a} = \sqrt{2a^2} \cdot \sqrt{a} = a\sqrt{2a} \][/tex]
- Now, multiply:
[tex]\[ \sqrt{2a} \cdot \sqrt{2a^3} = \sqrt{2a} \cdot (a\sqrt{2a}) = a (\sqrt{2a} \cdot \sqrt{2a}) = a \cdot \sqrt{4a^2} = a \cdot 2a = 2a^2 \][/tex]
3. Combine the parts:
Now we have:
[tex]\[ \sqrt{2a} \left(4\sqrt{2a} + a\sqrt{2a}\right) = \sqrt{2a}(4\sqrt{2a}) + \sqrt{2a}(a\sqrt{2a}) \][/tex]
Simplify each term:
[tex]\[ 4\sqrt{2a} \cdot \sqrt{2a} = 4 \cdot (\sqrt{2a})^2 = 4 \cdot 2a = 8a \][/tex]
[tex]\[ \sqrt{2a} \cdot (a\sqrt{2a}) = a \cdot \sqrt{2a} \cdot \sqrt{2a} = a \cdot 2a = 2a^2 \][/tex]
Adding these terms together:
[tex]\[ 8a + 2a^2 \][/tex]
Hence, the simplified expression is:
[tex]\[ \boxed{2a^2 + 8|a|} \][/tex]
Given: [tex]\(\sqrt{2a}\left(2 \sqrt{8a} + \sqrt{2a^3}\right)\)[/tex]
1. Simplify [tex]\(\sqrt{2a} \cdot 2\sqrt{8a}\)[/tex]
- First, consider [tex]\(\sqrt{8a}\)[/tex]:
[tex]\[ \sqrt{8a} = \sqrt{4 \cdot 2a} = \sqrt{4} \cdot \sqrt{2a} = 2\sqrt{2a} \][/tex]
- Next, multiply by 2:
[tex]\[ 2\sqrt{8a} = 2 \cdot 2\sqrt{2a} = 4\sqrt{2a} \][/tex]
2. Now, simplify [tex]\(\sqrt{2a} \cdot \sqrt{2a^3}\)[/tex]
- Consider [tex]\(\sqrt{2a^3}\)[/tex]:
[tex]\[ \sqrt{2a^3} = \sqrt{2a^2 \cdot a} = \sqrt{2a^2} \cdot \sqrt{a} = a\sqrt{2a} \][/tex]
- Now, multiply:
[tex]\[ \sqrt{2a} \cdot \sqrt{2a^3} = \sqrt{2a} \cdot (a\sqrt{2a}) = a (\sqrt{2a} \cdot \sqrt{2a}) = a \cdot \sqrt{4a^2} = a \cdot 2a = 2a^2 \][/tex]
3. Combine the parts:
Now we have:
[tex]\[ \sqrt{2a} \left(4\sqrt{2a} + a\sqrt{2a}\right) = \sqrt{2a}(4\sqrt{2a}) + \sqrt{2a}(a\sqrt{2a}) \][/tex]
Simplify each term:
[tex]\[ 4\sqrt{2a} \cdot \sqrt{2a} = 4 \cdot (\sqrt{2a})^2 = 4 \cdot 2a = 8a \][/tex]
[tex]\[ \sqrt{2a} \cdot (a\sqrt{2a}) = a \cdot \sqrt{2a} \cdot \sqrt{2a} = a \cdot 2a = 2a^2 \][/tex]
Adding these terms together:
[tex]\[ 8a + 2a^2 \][/tex]
Hence, the simplified expression is:
[tex]\[ \boxed{2a^2 + 8|a|} \][/tex]
Thank you for contributing to our discussion. Don't forget to check back for new answers. Keep asking, answering, and sharing useful information. For trustworthy and accurate answers, visit IDNLearn.com. Thanks for stopping by, and see you next time for more solutions.